Breastfeeding and HIV: experiences from a decade of prevention of postnatal HIV transmission in sub-Saharan Africa - van Esterik Penny; Sellen Daniel W; de Paoli Marina M; Moland Karen; Leshabari Sebalda C; Blystad Astrid (BMC, 2010)
Abstract Infant feeding by HIV-infected mothers has been a major global public health dilemma and a highly controversial matter. The controversy is reflected in the different sets of WHO infant feeding guidelines that have been issued over the last two decades. This thematic series, 'Infant feeding and HIV: lessons learnt and ways ahead' highlights the multiple challenges that HIV-infected women, infant feeding counsellors and health systems have encountered trying to translate and implement the shifting infant feeding recommendations in different local contexts in sub-Saharan Africa. As a background for the papers making up the series, this editorial reviews the changes in the guidelines in view of the roll out of prevention of mother to child transmission (PMTCT) programmes in sub-Saharan Africa between 2001 and 2010.